A qualitative exploration of expert perspectives on applying the science of learning to higher education - Nugent, Annita; Carroll, Annemaree; Lodge, Jason M.; Matthews, Kelly E.; MacMahon, Stephanie; Sah, Pankaj (Frontiers in Education, 2023)
Amid the constant change in higher education, a clear-eyed focus on the mission of higher education to support student learning is critical. Supporting student success, in turn, needs to emphasise rigorous evidence about what matters most for facilitating high-quality learning.With the science of learning, an emerging interdisciplinary field, as the study foundation, a series of 20 interviews was conducted with senior academics with research expertize in higher education and learning sciences. Interviews focused on principles for effective learning in the 21st century and relevance of science of learning research and literature to these principles. Using inductive and deductive thematic analysis across six iterative phases, seven key themes critical to contemporary higher education learning emerged, from which the higher education learning principles were developed. The principles provide a powerful tool to guide effective university teaching at an individual, organisation and policy level.